The impact of agribusiness sustainability practices on economic growth - Ichdayati, Lilis Imamah; Rochaeni, Siti; Maman, Ujang; Samad, Abdul Wahab; Utama, Zahera Mega (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate how sustainability practices in the agribusiness sector contribute to sustainable economic growth within the green economy framework. The research employs the Smart PLS analytical method to examine the influence of agribusiness activities, renewable energy use, green technology adoption, Environmental, Social, and Governance (ESG) principles, and workforce welfare on business and economic sustainability. Findings reveal that agribusiness and green technology adoption are crucial drivers of business sustainability, which subsequently enhances economic sustainability. Additionally, workforce welfare significantly supports the uptake of green technology, indicating that well-supported human resources stimulate environmentally friendly innovation. The study concludes that embedding sustainability practices into agribusiness strategies is essential not only for achieving immediate economic gains but also for promoting long-term, inclusive economic growth. Practically, these insights offer valuable guidance for business actors and policymakers aiming to develop an adaptive agribusiness sector responsive to environmental and social dynamics.